PENGARUH PERTUMBUHAN EKONOMI TERHADAP PENGANGGURAN DI PROVINSI ACEH - Ricky Ricky; Cut Zakia Rizky (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2021)
Abstract Aceh Province is one of the provinces with the highest unemployment rates in Indonesia. This study aims to analyze the influence of economic growth on unemployment rate in Aceh Province. The data used in this study is in the period 1989-2018 and analysis model used is ordinary linear regression. The results of this study indicate that the economic growth variable has a negative and not significant effect on Aceh’s unemployement rate. This study also illustrates that the Okun Law doesn’t effective in Aceh Province because of its low significant effect. The reduction of Unemployment rate in Aceh is very much influenced by other factors. The results of this study are expected to be an indicator of the government in choosing policies that are appropriate to reduce unemployment in Aceh Province. Keywords: Economic Growth, Unemployment Rate, Aceh Province